Recurso especial de doble conforme como garantía del imputado en sentencias de la corte provincial de justicia de Imbabura, 2022- 2023: factibilidad de su aplicación - Isacas Pozo, Rosalía Lizbeth (2024)
The present investigation is carried out base d on the special appeal of doble conformity as a guarantee of the accused in sentences of the Provincial Court of Justice of Imbabura, to determine its feasibility in the application. The special double compliance recourse arises from the need to have a new review that allows to ensure the criminal procedural guarantees of the accused, since the Ecuadorian State must ensure the remedies that guarantee the right to appel be feasible at the time of its application and they protect the rights and guarantees of the procedural parts, in this case the accused. The double jeopardy recourse is an exclusive recourse of the defendant. The general objective is to determine the feasibility of protection of the criminal procedural guarantees of the accused when filing the double jeopardy recourse of the Provincial Court of Imbabura of the Specialized Criminal, Military Criminal, Police Criminal and transit Court of the period 2023, through the analisis of cases and doctrine, in order to determine the advantages of this recourse. The approach was qualitative, the leve lof Depth desctptive, the methods Normative, hermeneutic and deductive, which allowed to analyze the information gathered through the documentary review technique, the result is the generic criminal procedural guarantees in normative, doctrinal and jurisprudential forms are protected by the double jeopardy resourse, but at the time of its application it is a mere utopia because it violates the guarantee of due process and effective judicial protection base on the principle of celerity. Finally, it is recommended the National Court of Justice create a Specialized Chamber with competence, takes cognizance and resolves the recourse of double conformity in order to protect the procedural guarantees of the accused.